Integral field spectroscopy of Green Peas - I. Disentangling disc-like turbulence and strong outflow kinematics in SDSS J083843.63+385350.5 - Bosch, Guillermo Luis (2019)
Integral field spectroscopy is well known for providing detailed insight of extended sources thanks to the possibility of handling space resolved spectroscopic information. Simple and straightforward analysis such as single line fitting yields interesting results, although it might miss a more complete picture in many cases. Violent star-forming regions, such as starburst galaxies, display very complex emission line profiles due to multiple kinematic components superposed in the line of sight. We perform a spatially resolved kinematical study of a single Green Pea (GP) galaxy, SDSS J083843.63+385350.5, using a new method for analysing integral field unit observations of emission line spectra. The method considers the presence of multiple components in the emission line profiles and makes use of a statistical indicator to determine the meaningful number of components to fit the observed profiles. We are able to identify three distinct kinematic features throughout the field and discuss their link with a rotating component, a strong outflow, and a turbulent mixing layer.We also derive an updated star formation rate for SDSS J0838 and discuss the link between the observed signatures of a large-scale outflow and of the Lyman continuum leakage detected in GP galaxies.